Prosociality Spillovers of Working with Others - Michalis Drouvelis; Benjamin Marx (Center for Economic Studies and ifo Institute (CESifo), 2018)
Group compensation and public announcement of performance are two common aspects of working with other people. We randomly assign these aspects to real-effort tasks. Following task completion and payment, subjects are given an unexpected opportunity to donate to a local charity. Group compensation and public announcement of performance have little effect on work performance but striking spillover effects on subsequent donations. Public announcement of performance doubles the amount donated to charity, and group compensation significantly increases the share donating. The results suggest that interpersonal interactions in the workplace environment may have important spillover effects on prosocial behavior outside of work.
Keywords: D01; D64; A13; 330; prosocial; spillover; charitable; group; experiment